Stock assessment of Crossocheilus diplochilus (Heckel, 1838) in Dal Lake of Kashmir Himalayas - Sinan Nissar; Tabasum Yousuf; Yahya Bakhtiyar (Journal of Fisheries, 2025)
The intricate dynamics governing population parameters stand as pivotal pillars in the realm of fish management and conservation. Accordingly, the various parameters of population dynamics of Crossocheilus diplochilus (Heckel, 1838) from the Dal Lake of Kashmir valley were investigated. The study reported that the fish exhibits a length range of 5.4 to 14.8 cm and a weight range of 1.24 to 17.19 g. The b value was reported to be 2.9 depicting negative allometric growth. The Fulton and relative condition factors were reported to be 0.86 and 0.99 respectively. The growth constant, asymptotic length, age at zero length and growth performance index were reported to be 0.33 year–1, 17.40 cm, –0.62 years and 2.0 respectively. Fishing mortality was found to be higher than the natural mortality. The exploitation ratio was reported to be 0.52 which was found to be lower than the exploitation rate producing maximum yield (0.81). This is suggestive of an underexploited state of fishery of C. diplochilus from this lake.